The Effect of Halal Awareness, Halal Certification, and Social Servicecafe on Purchase Intention in Indonesia: The Mediating Role of Attitude - Shahnia, Citra; Permana, Dudi; Harini, Sri; Endri, Endri; Wahyuningsih, Mutia (International Review of Management and Marketing, 2024)
The research aims to determine the effect of Halal awareness, Halal certification, and social Servicescape on the purchase intention of Halal food, which is mediated by attitude towards Japanese food products. The research was conducted on 256 respondents who like Japanese ramen noodles. The determination of purposive sampling technique is used in this research. The research approach is the Structural Equation Model (SEM) with Smart-PLS analysis tool. The intention to buy Halal Food still needs to be considered in several aspects, such as certification, Halal Awareness, and social services, to lead the attitude to decide to buy Halal foods. The research is only focused on one Japanese restaurant, while the object of the study still needs to be comprehensive. In the next few years, it is hoped that the government will increase the counseling related to the “Indonesia is going to be the center of world’s Halal” program and decide on new, more exciting programs related to the Halal Industry. Furthermore, producers encourage companies to implement more stringent processes for security, cleanliness, and the packaging process for goods distribution to be marketed. The value of this research is to determine the consumers’ trust in continuing to visit Japanese restaurants, though there needs to be more clarity on the restaurant’s Halal certification.